THE PROGNOSTICATION OF WATER RESERVOIR EUTROPHICATION PROCESSES ON THE EXAMPLE OF THE VORSKLA RIVER - Pysarenko, P. V.; Korchagin, O. P. (Scientific Progress & Innovations, 2019)
The article deals with investigating the eutrophication process of natural water reservoirs. It has been mentioned that at present the development of theoretical foundations and search of practical measures in fighting mass development of cyanic bacteria in top layer water reservoirs are being actively conducted, which requires deep analysis and modeling eutrophication processes. Thus, the aim of the paper is studying the factors causing eutrophication of top layer water on the example of the Vorskla river and developing mathematical dependence models of the above mentioned factors and modeling the processes of water quali-ty management based on the concept of nutrient limit. The research methods included conducting analytical, natural, laboratory studies, and also the calculation part. To investigate eutrophication process of water in the Vorskla river samples were taken 0.2−0.5 m deep from the water reservoir top layer (in different districts of the town of Poltava and its outskirts). Based on the obtained results it was established that the higher ni-trogen and phosphorus content in the water was, the higher was the content of cyanic bacteria, which corre-spondingly increased the eutrophication process. To model the processes of eutrophication stationary one-dimensional model was developed, including the following variables: chlorophyll concentration (character-izing the concentration of phytoplankton), the concentrations of phosphorus orthophosphate, ammonium ni-trogen, nitrate nitrogen, and phosphorus, restored from bottom sediments. The modeling of biogenic sub-stances’ dynamics in the basin of the Vorskla river was conducted. It was found that the increasing of blue and green algae biomass caused a sharp decreasing of nitrogen concentration. This effect is explained by incoming of ammonium nitrogen with sewage water, processing ammonia to nitrates by bacteria, and also transferring impurities into the river basin. The results of mathematical water quality modeling showed that affecting the process of eutrophication limitation resulted in increasing the concentration of nutrients and decreasing phytoplankton concentration. The conducted modeling of the processes of water quality man-agement (on the example of the Vorskla river) based on using target function enabled to determine the opti-mal content of biogenic substances, which can maintain the optimal chlorophyll content. Using the strategy, based on the concept of nutrients’ limit enabled to define the optimal nitrate nitrogen content (2 mg/l and less), at which the growth of cyanic bacteria was not intensified. The obtained results enable to prognosti-cate mass appearing of cyanic bacteria in water reservoirs in summer and develop the measures of fighting this negative phenomenon.